2017
DOI: 10.4067/s0718-58392017000300266
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient content, fat yield and fatty acid profile of winter rapeseed ( Brassica napus L.) grown under different agricultural production systems

Abstract: Quality features of rapeseeds (Brassica napus L.) and potential for high yielding to a major extent may be defined by improvements in agricultural engineering methods that encompass biological progress. However, this is associated with fertilization and application of pesticides, which may negatively impact on environment and quality. It is thus essential to develop and improve edible oil production systems to satisfy farmer and non-threatening consumer. The aim of this study was to evaluate content of nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Fordoński et al (2015) showed higher contents of the micronutrients Fe, Cu, Zn and Mn in rape seeds grown after faba bean, pea, and white lupine than after spring wheat. However, Stępień et al (2017) obtained a higher level of Zn and Mn in rape seeds grown in the high-input technology and Fe in the medium-input technology. In conclusion, it was found that the foliar fertilizer Insol 5 affected a significant increase in yield and a change in the chemical composition of seeds.…”
Section: Measurements Of Indexes and Leaf Stomatal Conductivitymentioning
confidence: 86%
“…Fordoński et al (2015) showed higher contents of the micronutrients Fe, Cu, Zn and Mn in rape seeds grown after faba bean, pea, and white lupine than after spring wheat. However, Stępień et al (2017) obtained a higher level of Zn and Mn in rape seeds grown in the high-input technology and Fe in the medium-input technology. In conclusion, it was found that the foliar fertilizer Insol 5 affected a significant increase in yield and a change in the chemical composition of seeds.…”
Section: Measurements Of Indexes and Leaf Stomatal Conductivitymentioning
confidence: 86%
“…The nitrogen application in the production process of a selected crop for the producing of biofuels or biodiesel, has a major impact not only on the overall profitability of raw material systems for biofuel production but also on the environment [ 18 , 30 ]. For great interest of farmers in various oil crop alternatives, different levels of nitrogen fertilization (0, 50, 100, 150 kg/ha N) per oil content and fatty acid composition were observed in field trials in the southeastern United States [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [55,56] also reported a high positive correlation between oil content and seed yield. However, unlike our results, they did not find a significant correlation between oil content and oil yield.…”
Section: Discussionmentioning
confidence: 88%